THE ROLE OF THE UNITED NATIONS IN PROTECTING THE DIPLOMATIC AGENT - Wijdan Raham Khudhair (Scholar Express Journals, 2021)
The diplomatic employee's work is the most important  of works on the international level, Whether or time of international peace or war, And if this employee went through several stages and happened to the fact that the world is developing in relations and agreements according to the general international law, And the diplomat’s staff is still fraught with various dangers, Therefore, the United Nations has endeavored, since its foundation, to protect it through private and public treaties and agreements, Which included the rights and privileges of me as a diplomat’s employee, However, the employee, and with the development of the concept of international terrorism, was exposed to many risks and threats, It is through this study to define the concept of this employee and the protection that states and international personalities take.
Keywords: Diplomat; international responsibility; United Nations; international conventions; international terrorism; diplomatic missions